G38(P) The asthma big room: improving childhood asthma management. (May 2019) - Coughlan, C; McGeorge, E; Fawcett, M; Smith, A; Slade, C; Thompson, N; Hall, S; Klaber, R
Abstract : Introduction: Despite effective treatments and clear clinical guidelines, 13 children died from asthma in England and Wales in 2016. 1 Asthma accounts for a high proportion of paediatric hospital attendances, 75% of which are 'avoidable'. 2 Patients with a documented asthma care plan are less likely to present to hospital acutely, but coverage remains patchy. 3 This underpins the growing consensus that transforming asthma care requires improvement of existing services (QI) rather than paradigm shifts in diagnosis and treatments. Effective asthma management requires engagement of multiple stakeholders, including patients, carers, general practitioners (GPs), hospital doctors and specialist nurses. However, traditional models of healthcare delivery impede collaboration between these groups in co-designing service improvements. Methods: In late 2017, an 'Asthma Big Room' (ABR) was established at our large inner-city hospital. This QI forum derives from the 'Oobeya' model of lean management. 4 Stakeholders hold a weekly multidisciplinary team meeting with a flat hierarchy, managed by trained 'flow coaches'. The ABR facilitates interpretation of data relating to hospital admissions, care plan coverage and patient education; and the design and implementation of rapid tests of change. Stakeholders have created a shared vision of the steps needed to improve care across the region, captured in a 'driver diagram'. 'Patient stories' are brought to the ABR to provide a central clinical focus. Results: The ABR has engaged professionals from our Emergency Department (ED), ward and out-patient settings. Other attendees include local GPs, site practitioners and information technology specialists. Baseline audit indicated care plan coverage of 17% for children admitted in April 2018. Discussions in the ABR have led to the design of an electronic care plan which we aim to supply to all children who attend our ED or are admitted with asthma. Future projects devised in this forum include outreach clinics and group consultations. Conclusion: Big Rooms constitute a valuable means of engaging stakeholders in quality improvement, with multiple potential applications in Paediatrics. References: ONS. Death registrations in England and Wales, summary tables: 2016. https://www.ons.gov.uk/releases/deathregistrationsinenglandandwalessummarytables2016 PHE National Child and Maternal Health Intelligence Network. http://webarchive.nationalarchives.gov.uk/20170302112908/http://www.chimat.org.uk/resource/view.aspx?RID=101746&REGION=101634 Adams RJ, et al. Thorax 2000;55(7):566–73. Lawal AK, et al. Syst Rev 2014;3:103.